PENGARUH AKUPRESUR TITIK NEIGAUN (P6) DAN INHALASI AROMATERAPI CITRUS LEMON DALAM MENGURANGI FREKUENSI MUAL MUNTAH PADA IBU HAMIL TRIMESTER I : The Effect Of Neigaun Point Acupressure (P6) And Citrus Lemon Aromatherapy Inhalation In Reducing The Frequency Of Nausea Vomiting In First Trimester Pregnant Women - Ahmad, Najiah; Sapto Pramono, Joko; Suryani, Heni (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2023)
Nausea and vomiting in pregnancy are the reaction of the mother's body to the changes that occur as a result of pregnancy. Nausea and vomiting if not treated immediately will become Hyperemesis Gravidarum(HEG).Symptoms of nausea and vomiting in HEG can be prevented non-pharmacologically with acupressure therapy and citrus lemon aromatherapy. Aims the purpose of this study was to determine the effect of acupressure at the neigaun point (P6) and inhalation of citrus lemon aromatherapy in reducing the frequency of first trimesternausea and vomiting at Samarinda Medika Citra Hospital. Methods this study uses a true experimental design. The population is all first trimester pregnant women who experienced nausea and vomiting and underwent outpatient care at Samarinda Medika Citra Hospital. Sampling technique with consecutive sampling of 36 respondents. The results showed that there was a significant effect of giving acupressure at the neiguan point (P6) and inhaling citrus lemon aromatherapy in reducing the frequency of nausea and vomiting in pregnant women in the first trimester (p-value = 0,000). Nausea and vomiting can occur in first trimester pregnant women at 6-12 weeks of gestation. So that pregnant women are advised to do acupressure and inhalation of citrus lemon aromatherapy to reduce the frequency of nausea and vomiting which do not cause side effects